Competency Analysis and School Culture on Teacher Performance in Cimanggu District - Asep Saepulloh; Novianti Sisili; Muldiyana Muldiyana (International Journal of Education, Information Technology, and Others, 2022)
The purpose of this study was to determine the effect of competence and culture on teacher performance in Cimanggu District. The method used in this study is a survey method with a quantitative approach. Data collection techniques used instruments to measure competence, school culture and instruments to measure teacher performance. Based on the results of data analysis and hypothesis testing with path analysis calculations, the results show that 1) There is an influence of competence on teacher performance at the Cimanggu District Elementary School, with the acquisition of tcount 2.34 while ttable for = 00.5 is 1.53 because tcount is more larger than ttable. 2) There is a positive influence of school culture on teacher performance at Elementary Schools in Cimanggu District with the acquisition of tcount 3.99 while ttable for = 00.5 is 1.53 because tcount is greater than ttable. 3) There is a significant direct effect between competence and school culture on teacher performance with tcount 3.29 while ttable for = 00.5 is 1.53. Good performance can be achieved by the school culture and the competencies possessed by teachers